Effect of Microwave Frying on Moisture Transport and Oil Uptake in Fried Foods - Luna M., Efrain E. (Zamorano: Escuela Agrícola Panamericana, 2019., 2019)
The process of deep-frying potatoes dates from years around 1700 A.D. Despite being the most important method of preparations, deep-frying has remained the same since its origins. In the following study, microwave frying was compared against conventional frying at 177, 185 and 191 °C, furthermore, the addition of microwave energy after 1 minute of conventional frying was tested as well. Two different parameters were analyzed for each treatment: Oil Uptake and Moisture Transport. The effects of microwave energy in oil uptake were analyzed by measuring final fat content through Soxhlet extraction. Moisture transport was analyzed by measuring initial and final moisture content by freezing the samples in liquid nitrogen and then heating samples at 105 Celsius, with a posterior measurement weight loss. Microwave energy was found to increment moisture loss and oil uptake in the process of deep frying. It is speculated that microwave energy increases the energy inputted into the system, and thus it boosts water loss and therefore oil uptake after the frying finished. Temperature showed to have an impact in water loss but not in oil uptake. Said phenomenon can be explained by the fact that most of the oil absorbed by potatoes is absorbed after the frying process has been done. Further studies need to be done in order to give a deep and clear explanation of the effects of microwave energy on the complex process of deep frying.